2022
DOI: 10.1057/s41288-021-00257-z
|View full text |Cite
|
Sign up to set email alerts
|

Managing customer satisfaction: digital applications for insurance companies

Abstract: Customer satisfaction management is increasing in importance within the insurance industry. In particular, to define a customer-oriented strategy, installing digital applications based on technologies, e.g. including artificial intelligence or cloud computing, ranks among the major strategic challenges. Against this background, the aim of this paper is to take an integrated perspective on managing customer satisfaction and the digital transformation. Towards this end, we identify and assess a set of digital ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Asimismo, Eckert et al (2022) señala que la implementación de la transformación digital en el sector de compañías de seguros es fundamental, puesto que permite ofrecer soluciones convergentes necesarias a través de los sitios web y aplicaciones móviles mediante canales flexibles del comercio electrónico, permitiéndoles a través de las monitorear, crear tarifas, precios refinados, suscripciones digitales y sobre todo detectar fraude, a su vez acelerar y automatizar procesos disminuyendo los costos de materia prima, otorgándole un mejor servicio al cliente.…”
Section: Resultsunclassified
“…Asimismo, Eckert et al (2022) señala que la implementación de la transformación digital en el sector de compañías de seguros es fundamental, puesto que permite ofrecer soluciones convergentes necesarias a través de los sitios web y aplicaciones móviles mediante canales flexibles del comercio electrónico, permitiéndoles a través de las monitorear, crear tarifas, precios refinados, suscripciones digitales y sobre todo detectar fraude, a su vez acelerar y automatizar procesos disminuyendo los costos de materia prima, otorgándole un mejor servicio al cliente.…”
Section: Resultsunclassified
“…Thus, we predicted that there is a correlation between satisfaction in using the application and continous purchases or usages. In addition, Eckert et al (2022) stated that the willingness to revisit the application in making purchases reflects consumers' willingness to buy and recommend the application and the products within it. When consumers are satisfied and continue to use or purchase products and service in an application, they will prioritize the service as an optionwhen they decide to purchase.…”
Section: User Satisfaction and Continuous Purchase Behaviormentioning
confidence: 99%
“…Claims management means collecting, recording, analyzing, tracking, and settling claims (Farbmacher et al 2022). Insurtech companies use advanced technologies to improve customer experience and satisfaction to better respond to customers' demands (Eckert et al 2022). For instance, Che et al (2022) conducted a study on the impact of usage-based insurance (UBI) technologies on US insurance companies and found that the implementation of UBI enhances underwriting performance by reducing claims.…”
Section: Literature Reviewmentioning
confidence: 99%